Clinical and laboratory studies on four Chinese patients with succinate-CoA ligase deficiency noticed by mild methylmalonic aciduria - Liu, Y P (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2016)
OBJECTIVE: To study the clinical and genetic features of the patients with secondary methylmalonic aciduria due to succinate-CoA ligase deficiency